Floristic composition and spatial changes of roadside vegetation in the exposition notch on the example of Minsk and Minsk region highways - Shavalda, Yauheni S.; Stepanovich, Iosif M. (Journal of the Belarusian State University. Ecology, 2022)
The results of ecological and floristic studies of roadside phytocenoses during the passage of the road in the «notch» exposition are presented. The description of the vegetation along the transect line with the presented structure and species diversity was performed by dividing into 5 sectors depending on the distance from the roadway and the design of the right-of-way (ROW). The 5th sector was not taken into account in this work due to the interest in the plants of the anthropogenically disturbed territory of the ROW. A list of vascular plants and bryophytes has been compiled and analyzed, numbering 225 species that belong to 54 families, 167 genuses. The families with the largest number of species are Asteraceae, Poaceae, Fabaceae, Rosaceae, and Brassicaceae, which corresponds to the taxonomic characteristics of urban landscapes and roadside phytocenoses. A significant role of invasive species is specified: Echinochloa crus-galli (L.) P. Beauv, Conyza canadensis (L.) Cronq., Festuca arundinacea Schreb., Lepidotheca suaveolens (Pursh) Nutt. et al. Sectoral division made it possible to trace the effect of remoteness from the highway and changes in edaphic conditions on the species and ecological-coenotic composition of vegetation, their biomorphological spectrum according to the system of Ch. Raunkixr. For example, waterlogging and runoff of salt anti-icing agents in sectors 2 promotes the development of hygrophytic forms of plants and nitrophilic species: Phragmites australis (Cav.) Trin. ex Steud., Aegopodium podagraria L. et al. Erosion processes and soil underdevelopment cover in sectors 3 have a positive effect on the growth of halophytes and psammophytes: Oenothera biennis L., Sedum acre L. et al. According to the ecological-coenotic groups with the segetal-ruderal affiliation, forest (41 or 18,2 %) and meadow (40 or 17,8 %) species predominate, the contribution of plants characteristic of ruderal and meadow habitats is expressed (24 or 10,7 %), there are segetal-ruderal (23 or 10,2 %), ruderal (20 or 8,9 %), segetal (15 or 6,7 %) and ruderal-segetal (10 or 4,4 %) species.